2015
DOI: 10.4238/2015.august.7.18
|View full text |Cite
|
Sign up to set email alerts
|

Association between 1p13.3 genomic markers and coronary artery disease: a meta-analysis involving patients and controls

Abstract: ABSTRACT. Recently, genome-wide association studies on cardiovascular disease identified a series of associated single nucleotide polymorphisms in an intergenic region of chromosome 1p13.3. We investigated the association of this locus with cardiovascular disease in 13 case-control studies and undertook a meta-analysis for effect size, heterogeneity, publication bias, and strength of evidence. English and Chinese language articles were screened for the association of 1p13.3 single nucleotide polymorphisms with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…The minor G allele of the rs599839 variant in the PSRC1 gene showed a protective effect against CAD (OR ADD = 0.72, 95% CI: 0.56–0.92, p = 0.009; OR DOM = 0.66, 95% CI: 0.49–0.89, p = 0.007). In line with our results, the major allele A of this variant has been reported as a risk factor for CAD (OR = 1.29, 95% CI: 1.18–1.40) in European populations [ 13 ], and similar results were observed in meta-analysis in both Europeans (OR = 1.11, 95% CI: 1.08–1.15) [ 11 ] and Asians (OR = 1.31, 95% CI: 1.17–1.47) [ 21 ]. Besides, the minor allele G has been associated with a protective effect against the risk of CAD (OR = 0.422, 95% CI: 0.181–0.981) and lower levels of total cholesterol and LDLc in Indians [ 22 ].…”
Section: Discussionsupporting
confidence: 76%
“…The minor G allele of the rs599839 variant in the PSRC1 gene showed a protective effect against CAD (OR ADD = 0.72, 95% CI: 0.56–0.92, p = 0.009; OR DOM = 0.66, 95% CI: 0.49–0.89, p = 0.007). In line with our results, the major allele A of this variant has been reported as a risk factor for CAD (OR = 1.29, 95% CI: 1.18–1.40) in European populations [ 13 ], and similar results were observed in meta-analysis in both Europeans (OR = 1.11, 95% CI: 1.08–1.15) [ 11 ] and Asians (OR = 1.31, 95% CI: 1.17–1.47) [ 21 ]. Besides, the minor allele G has been associated with a protective effect against the risk of CAD (OR = 0.422, 95% CI: 0.181–0.981) and lower levels of total cholesterol and LDLc in Indians [ 22 ].…”
Section: Discussionsupporting
confidence: 76%
“…This locus contains the CELSR2-PSRC1-SORT1 gene cluster and it has been reported that the functional gene in this locus is SORT1 (10). The data we have obtained from epidemiological studies, cohort studies, and animal experiments have proven to us the strong relationship between sortie and lipid parameters (11)(12)(13). In addition, the effect of sortilin on the in ammatory process has been reported, independent of lipid parameters.…”
Section: Introductionmentioning
confidence: 52%
“…Therefore, the identi cation of gene regions known to have genetic effects on lipid pro les and their functional variants is very important in order to reduce the comorbidities of the disease by establishing early treatment protocols. In recent years, in studies conducted to determine predictors in CHD pathogenesis, a new candidate locus has been associated with CHD due to its effect on 1p13.3 lipid parameters (11)(12)(13)17). Although the complex scenario of sortilin's role in lipid metabolism has not been explained yet, according to the information we have obtained from experimental and functional studies, hepatic sortilin can act as a receptor for LDL-C, independent of its LDLR (18).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiyolojik çalışmalar, kohort çalışmaları ve hayvan deneyleri yapan çalışma gruplarının A. B. AKADAM-TEKER, E. TEKER verileri sortilin ve lipit parametreleri arasındaki güçlü ilişkiyi kanıtlar niteliktedir [11][12][13] . Ek olarak sortilin'in lipit parametrelerinden bağımsız olarak inflamatuar süreç üzerindeki etkisi de bildirilmiştir.…”
Section: Introductionunclassified